2019
DOI: 10.1093/jxb/erz367
|View full text |Cite
|
Sign up to set email alerts
|

GABA operates upstream of H+-ATPase and improves salinity tolerance in Arabidopsis by enabling cytosolic K+ retention and Na+ exclusion

Abstract: GABA has beneficial effects on salinity stress tolerance in Arabidopsis linked to increased activity of H+-ATPase, reduced ROS-induced K+ efflux from root epidermis, and increased SOS1 and NHX1 transcript levels in plant roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 59 publications
7
65
0
Order By: Relevance
“…There are few studies on the effect of exogenous GABA on the content of sodium ions in plants and it is not clear whether GABA can directly reduce sodium ion content. However, it has been reported that Arabidopsis mutants with high GABA content have signi cantly lower root sodium ux than those with low GABA content [1] Our study showed that Na + ux increased signi cantly under salt stress, and we also observed for the rst time that exogenous GABA signi cantly decreased Na + e ux in leaves and in ux in roots (Fig. 5).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…There are few studies on the effect of exogenous GABA on the content of sodium ions in plants and it is not clear whether GABA can directly reduce sodium ion content. However, it has been reported that Arabidopsis mutants with high GABA content have signi cantly lower root sodium ux than those with low GABA content [1] Our study showed that Na + ux increased signi cantly under salt stress, and we also observed for the rst time that exogenous GABA signi cantly decreased Na + e ux in leaves and in ux in roots (Fig. 5).…”
Section: Discussionsupporting
confidence: 68%
“…The ux of sodium ions in roots and leaves of salt-sensitive varieties were signi cantly higher than those of salttolerant varieties [36]. The content of sodium ion in leaves of a salt-sensitive Arabidopsis mutant was also signi cantly higher than that of a salt-tolerant mutant [1]. Therefore, we believe that the signi cant decrease of sodium ion ux and content by exogenous GABA is the important physiological mechanism of alleviating salt stress.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In recent years, soil salinization has become an alarmingly severe problem, affecting 10% of the land surface in the world [1] as well as 42.9% of protected soil in China [2]. This issue has become the main obstacle for the sustainable production of protected agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…However, soil salinization often severely affects tomato fruit yield and quality by decreasing photosynthetic efficiency and disturbing physiological metabolism due to ion toxicity, osmotic stress, nutrient deficiency, etc. Apparently, compared with the slow progress of breeding [1], the regulation of salt stress tolerance by exogenous substances is a fast and effective method to relieve salt damage in crops, especially by regulating various ion transport pathways and the related metabolism.…”
Section: Introductionmentioning
confidence: 99%